Safety and reliability methodology and applications, proceedings of the European Safety and Reliability Conference, ESREL 2014, Wrocław, Poland, 14-18 September 2014 - Nowakowski, Tomasz; Mlynczak, Marek; Jodejko-Pietruczuk, Anna; Werbinska-Wojciehowska, Sylwia (A Balkema Book, 2015)
Within the last fifty years the performance requirements for technical objects and systems were supplemented with: customer expectations (quality), abilities to prevent the loss of the object properties in operation time (reliability and maintainability), protection against the effects of undesirable events (safety and security) and the ability to restore performance (resilience). The need to adapt the operation of complex systems in such an uncertain and volatile environment has caused the necessity to formulate new and well established achievements associated with modeling, testing and evaluation of these properties